Evaluasi Dosen Berbasis Web (Studi Kasus pada Universitas Tanri Abeng) - Johny Hizkia Siringo Ringo; Rifqi Fadhil Ekaputra (Jurnal SISKOM-KB (Sistem Komputer dan Kecerdasan Buatan), 2019)
The basis of this research is to modernize the lecturer evaluation process which is still manually done and paper-based, becomes web-based with online feature, which of course will provide numerous benefits for all parties, including the students, lecturers, and academic staffs. The development of this system utilizes SDLC (Systems Development Life Cycle) method which is done phase-by-phase starting from system planning, requirement analysis, design, implementation, and ended by maintenance phase. This web-based system is using CodeIgniter PHP as its programming framework, complemented by other web-based elements such as HTML, CSS, and JavaScript. Additionally, MySQL is also used as the database to store all data within the system.